Gen Z’s Adoption of Investment Platforms: The Roles of Awareness, Literacy, and Risk Perceptions - Gularso, Kurnadi; Nicola, Nicola (Journal of Business & Applied Management, 2025)
The rapid proliferation of stock investment applications in Indonesia has not been matched by consistent adoption among Generation Z, revealing a research gap in understanding how psychological and risk-related factors shape the transition from awareness to actual usage. This study aims to examine the effects of awareness, financial literacy, and perceptions of reliability, security, and risk on Gen Z’s adoption of stock applications in urban contexts. A quantitative approach was employed through a survey of 130 Gen Z respondents and analysed using the PLS-SEM method. Results show that awareness enhances financial literacy and perceptions of reliability and risk but does not directly influence adoption. Reliability, security, and risk factors significantly affect adoption behavior and mediate the awareness–adoption link, while financial literacy does not function as a mediator. Theoretically, this study advances the UTAUT framework by integrating risk perception as a critical determinant of financial technology adoption. Managerially, the findings highlight that FinTech providers should enhance transparency of security features, foster trust-based communities, and design targeted digital education to encourage sustained adoption. Regulators may leverage these insights to implement consumer protection policies that strengthen trust and risk management, thereby accelerating the shift from awareness toward consistent usage of investment platforms.